Solid-Pseudopapillary Tumor of the Pancreas: A Single Center Experience - Valentina Beltrame; Gioia Pozza; Enrico Dalla Bona; Alberto Fantin; Michele Valmasoni; Cosimo Sperti (Gastroenterology Research and Practice)
Aim of this study was to review the institutional experience of solid-pseudopapillary tumors of the pancreas with particular attention to the problems of preoperative diagnosis and treatment. From 1997 to 2013, SPT was diagnosed in 18 patients among 451 pancreatic cystic neoplasms (3.7%). All patients underwent preoperative abdominal ultrasound, computed assisted tomography, and tumor markers (CEA and CA 19-9) determinations. In some instances, magnetic resonance, positron emission tomography, and endoscopic ultrasound with aspiration cytology were performed. There were two males and 16 females. Serum CA 19-9 was slightly elevated in one case. Preoperative diagnosis was neuroendocrine tumor (n=2), mucinous tumor (n=2), and SPT (n=14). Two patients underwent previous operation before referral to our department: one explorative laparotomy and one enucleation of SPT resulting in surgical margins involvement. All patients underwent pancreatic resection associated with portal vein resection (n=1) or liver metastases (n=1). One patient died of metastatic disease, 77 months after operation, and 17 are alive and free with a median survival time of 81.5 months (range 36–228 months). Most of SPT can be diagnosed by CT or MRI, and the role of other diagnostic tools is very limited. We lack sufficient information regarding clinicopathologic features predicting prognosis. Caution is needed when performing limited resection, and long and careful follow-up is required for all patients after surgery.